Different rates of cognitive decline in autosomal dominant and late‐onset Alzheimer disease. Issue 10 (2nd December 2021) - Buckles, Virginia D.; Xiong, Chengjie; Bateman, Randall J.; Hassenstab, Jason; Allegri, Ricardo; Berman, Sarah B.; Chhatwal, Jasmeer P.; Danek, Adrian; Fagan, Anne M.; Ghetti, Bernardino; Goate, Alison; Graff‐Radford, Neill; et al.
Abstract: As prevention trials advance with autosomal dominant Alzheimer disease (ADAD) participants, understanding the similarities and differences between ADAD and "sporadic" late‐onset AD (LOAD) is critical to determine generalizability of findings between these cohorts. Cognitive trajectories of ADAD mutation carriers (MCs) and autopsy‐confirmed LOAD individuals were compared to address this question. Longitudinal rates of change on cognitive measures were compared in ADAD MCs (n = 310) and autopsy‐confirmed LOAD participants (n = 163) before and after symptom onset (estimated/observed). LOAD participants declined more rapidly in the presymptomatic (preclinical) period and performed more poorly at symptom onset than ADAD participants on a cognitive composite. After symptom onset, however, the younger ADAD MCs declined more rapidly. The similar but not identical cognitive trajectories (declining but at different rates) for ADAD and LOAD suggest common AD pathologies but with some differences.